FAKTOR YANG MEMPENGARUHI BRAND TRUST KONSUMEN ONLINE TRAVEL AGENT TIKET.COM - Nadia Tammy Wijaya; Arry Widodo (Jurnal Riset Bisnis dan Manajemen, 2020)
Online travel sales at the world level are getting higher every year. Online travel bookings are the biggest part of consumer e-commerce spending in 2018. However, the proliferation of online travel agents is unfortunately not in tune with consumer brand trust in certain brands or sites, according to survey conducted by Nielsen,it is stated that 60% of consumers in Indonesia do not really trust online stores, they are hesitant to give out their personal information. This study aims to find out how the brand trust of consumers towards the online travel agent (OTA) Tiket.com in Jakarta is. This research uses quantitative research methods and a descriptive-causal approach, with Structural Equation Modeling (SEM) analysis technique using SMART PLS 3.0 software. The results showed that privacy, word of mouth, and good online experience had a positive and significant effect on the ticket.com consumer brand trust in Jakarta, while security, quality of information and brand names had a positive but not significant effect on the consumer brand trust tiket.com in Jakarta.